CBCT Evaluation of Quality and Quantity of Bones for Immediate Implant Treatment Planning in Central Incisor Area in relation to Arch Form. (17th April 2023) - Hassan, Nuhad A.; Al-radha, Afya Sahib Diab
Abstract : Understanding the quality of the ridge and facial cortical bone in the aesthetic zone is important for treatment with an immediate dental implant. This study aimed to analyze bone density and widths of the facial cortical bone and alveolar ridge at the central incisors in relation to arch form. A total of 400 teeth from 100 cone-beam CT images were divided equally between the upper and lower central incisors. The central incisor area was assessed for the width of the facial cortical and alveolar bones at three different points (3 mm, 6 mm, and 9 mm from the cementoenamel junction). Arch forms and densities of cortical and cancellous bones in the interradicular regions were evaluated. The difference in facial cortical bone thickness at 3 points was smaller for the upper teeth than for the lower teeth on both sides. The alveolar bone width was higher in the maxilla than the mandible with highly significant differences (P < 0.001 ). The highest bone density was at the buccal aspect of the mandible (897.36 ± 136.72 HU), while the lowest density was at the cancellous bone of the maxilla (600.37 ± 126.63 HU). The dominant arch form was ovoid 71%, followed by square 20% and the tapering arch form 10%. The tapering arch form has the highest alveolar bone width in the upper jaw without statistical significance. The facial cortical bone thickness needs to be evaluated before implantation in the anterior region because it is less than two millimeters in both jaws. CBCT is important for the immediate implant. The ovoid shape was the dominant arch form.